Pengaruh Manajemen GAP, Modal, Likuiditas, Risiko Pembiayaan, Tingkat Efisiensi dan Ukuran Bank (Size) terhadap Net Interest Margin pada Bank Syariah Mandiri, Bank BRI Syariah dan Bank BNI Syariah Tahun 2015-2019 - Inna Cikita Mahdatika; Atina Shofawati (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
Net Interest Margin (NIM) is an indicator of the operational efficiency of a bank which is considered an important instrument used to assess the ability of effectiveness and managerial efficiency in utilizing bank resources and is also very important for controlling bank spending. This study aims to determine the relationship between Gap Management, Capital, Liquidity, Financing Risk, Efficiency Level and Bank Size (Size) on Net Interest Margin (NIM) at Mandiri Sharia Bank, BRI Sharia and BNI Sharia 2015-2019. Using panel data regression support with Random Effect Methods (REM). The results showed that simultaneously all exogenous variables have a significant effect on the endogenous variable Net Interest Margin (NIM). Partially the Gap Management and Liquidity variables have a significant positive effect on Net Interest Margin (NIM). Meanwhile, the variables of Capital and Bank Size have a significant negative effect on Net Interest Margin (NIM). However, the variable financing risk and efficiency level did not have a significant effect on the Net Interest Margin (NIM) at PT. Bank Syariah Mandiri Tbk, PT. Bank BNI Syariah Tbk, PT. BRI Syariah Tbk.